MISCELLANEOUS BOTANICAL NOTES 3 - Kostermans, A.J.G.H (REINWARDTIA, 1962)
1. Lauraceae. New combinations: Beilschmiedia gitingensis (Endiandra gitingensis Elmer); B. zapoteoides (Endlicheria zapoteoides Lundell); Persea sphaerocarpa (Beilschmiedia sphaerocarpa Winkler) ; Alseodaphne andersoni (Cryptocarya andersoni King ex Gamble). New species; Beilschmiedia reticulata (Borneo), Litsea palustris (Borneo), Ocotea trinuladensis (Trinidad). Reductions: Cryptocarya macrophyllaGamble = Cr. caloneura (Scheff.) Kosterm.; Alseodaphne keenanii Gamble Alseodaphne andersoni (King ex Gamble) Kosterm.; Litsea bancana (Miq.) Boerlage = Beilschmiedia madang Bl.2. Leguminosae - Mimosaceae: Abarema sumbawaensis, nov. spec; Abaremakarmsii (von Malm) Kosterm., descript. emend.3. Sterculiaceae: A note on Heritiera and Tarrietia and on H. pericoriacea Kosterm.; Heritiera gigantea, spec. nov. (Sumbawa) ; Firmiana sumbawaensis, spec. nov.4. Verbenaceae: Teijsmanniodendron glabrum Merrill reinstated.5. Septogarcinia sumbawaensis, nov. gen., nov. spec. (Guttiferae).6. Mammea timorensis Kosterm., descript. emend.